Analisis Kesulitan Mahasiswa Pendidikan Matematika dalam Menyusun Latar Belakang Penelitian Skripsi - Muhammad Ridlo Yuwono (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
This study aims to analyze the difficulties of students in compiling a thesis research background. This research is included in descriptive qualitative research that uses a case study approach to analyze the difficulties of students in preparing the background for thesis research. The subjects taken in this study were students of the Mathematics Education Study Program, Widya Dharma University Klaten who took the thesis course. The data collection method in this study used the documentation method, the observation method and the interview method. The method triangulation technique was used to obtain valid data in this study. The instrument in this study used the main instrument and auxiliary instrument. The main instrument is the researcher who has a role to collect data in this study. Auxiliary instruments consist of two types, namely observation sheets and interview guides. Data analysis in this study uses the analytical model of Miles, Huberman and Saldana (2014) which consists of data condensation, data presentation and conclusion drawing. The results of this study are students have difficulty in (1) identifying the problem (2) focusing on the main research problem, (3) identifying the importance of solving the main problem, (4) reviewing previous research, (5) analyzing the shortcomings of previous research, and (6) reviewed other literature to correct the shortcomings of previous studies.